Rhizobacterium Bacillus cereus induces root formation of pepper (Piper nigrum L.) stem cuttings - Ab Aziz, Zakry Fitri; Mohd Saud, Halimi; Kundat, Franklin Ragai; Jiwan, Make; Wong, Sing King (Research in Biotechnology, 2015)
Rhizobacteria have been widely reported with beneficial properties, able to promote growth and yield of various agricultural crops. In the present study, two strains of rhizobacterium Bacillus cereus were tested on its ability to induce and elongate roots of pepper stem cuttings after inoculation. Results showed that B. cereus UPMLH24 inoculation on fresh pepper stem cuttings stimulated root number (55% increase over control), length of longest root (25% increase over control), total root length (87% increase over control), root fresh weight (28% increase over control) and root dry weight (112% increase over control). Present study recommends Bacillus cereus UPMLH24 as a potential candidate in a formulation of a biostimulant for organic and sustainable nursery for pepper production.